Network effects, spillovers and market structure - Behringer, Stefan (The Manchester School, 2014)
This paper investigates the effect of spillovers in a model of endogenous technical change resulting from network effects as can be, for example, found in the market for hand-held video consoles on the existence of a lower bound to market concentration.